Role of contrast-free MR-perfusion in the diagnosis of potential epileptogenic foci in children with focal epilepsia - M. V. Polyanskaya; A. A. Demushkina; I. G. Vasiliev; H. Sh. Gazdieva; A. A. Kholin; N. N. Zavadenko; A. A. Alikhanov (Эпилепсия и пароксизмальные состояния, 2018)
ASL (Arterial Spin Labeling) – a novel modality of MR angiography – is based on radio-frequency labeling of aqueous protons in the arterial blood; the method is used to monitor blood supply to  organs, including the brain. So far there has been little information on the use of ASL in children with focal epilepsy, especially in the pre-surgery period.Aim: to evaluate the perfusion patterns in seizure-free children with drug resistant focal epilepsy (FE) using the ASL mode of MRI.Materials and methods. We studied the ASL data of 54 (23-boys/31 girls) patients with FE  treated in the Dpt. of Neurology at the Russian State Children Hospital from 2015 to 2018. The  patients’ age varied from 4 months to 17 years. All images were produced with a 3T GE Discovery  750W system.Results. We found several brain perfusion patterns in children with FE; among other factors, those patterns depended on the clinical status of the patient, i. e. the interictal period or the early post- seizure period. The main pattern of the interictal period was characterized by a focal decrease in  perfusion located around a structural focus identified on MRI scans. In the early post-seizure  period, there was an increase in the arterial perfusion in the area of a structural epileptogenic lesion.Conclusion. ASL-MRI is an effective diagnostic method providing more information on children  with FE during their pre-surgery phase. The ASL modality needs further research to rationalize its wider use as a preferred diagnostic tool or as a combination with the more complex PET and SPECT.